A trans-umbilical single-site plus one robotic-assisted surgery for choledochal cyst resection in children - Lin, Yucan; Chen, Shan; Lin, Yang; Zhang, Ling; Wang, Jianbin; Qiu, Xinyi; Xu, Di; Li, Lizhi (Frontiers in Pediatrics, 2024)
Objective The purpose of this study is to compare the intraoperative and postoperative outcomes of a trans-umbilical single-site plus one robot-assisted surgery and a trans-umbilical single-site laparoscopic surgery in the treatment of choledochal cysts. Methods We retrospectively analyzed clinical data from 49 children diagnosed with choledochal cysts who were admitted to our hospital between June 2020 and December 2023. Among these patients, 24 underwent a trans-umbilical single-site plus one Da Vinci robot-assisted surgery (the robot group) and 25 underwent a trans-umbilical single-site laparoscopic-assisted surgery (the laparoscopic group). We compared differences in intraoperative and postoperative outcomes between the two groups. Results There was no significant difference between the two groups of patients in terms of gender, age, weight, clinical symptoms, maximum cyst diameter, type, postoperative complications, and facial expression, leg movement, activity, crying, and comfortability (FLACC) scoring (p > 0.05). Compared with the patients in the laparoscopic group, those in the robot group had less intraoperative bleeding [10 (8–12) vs. 15 (11.5–18) ml, p < 0.001] and required less postoperative drainage tube indwelling time [5 (4–6) vs. 7 (5.5–8) day, p < 0.001], less postoperative fasting time [4 (3–4) vs. 6 (5–7) days, p < 0.001], and less postoperative hospitalization time [6 (6–7) vs. 8 (6–10) days, p < 0.001], but they required more operative time [385.5 (317.0–413.3) vs. 346.0 (287.0–376.5) min, p = 0.050] and consumed more hospitalization expenses (79,323 ± 3,124 vs. 31,121 ± 2,918 yuan, p < 0.001). Conclusion The results of this study showed a shorter hospitalization time, quicker postoperative recovery, and less tissue damage but a higher cost and a longer operation time in patients who chose robotic surgery rather than laparoscopic surgery. With the continuous expansion of the scale of installed robot-assisted surgical systems and the gradual accumulation of the technical experience of surgeons, robot-assisted surgery may slowly surpass, and shows a trend to replace, laparoscopy because of its advantages.